Billolivia cadamensis (Gesneriaceae), a new species from Central Vietnam - Dat, Nguyen Quoc; Cuong, Nguyen Hieu; Long, Vu Ngoc; Truong, Luu Hong (Academia Journal of Biology, 2016)
Billolivia cadamensis (Gesneriaceae) is described as a new species from the central province of Quang Ngai, Vietnam. The new taxon is close to B. tichii but differs in shorter stem, abaxially glabrous bracts, calyx divided into 5 lobes to base, outside pubescent apical half of corolla tube, oblong or deltoid corolla lobes, dense hairs on apical 3/4 of the ovary and white corolla lobes. A key to all known species of Billolivia of Vietnam is given. Received 3 November 2016, accepted 27 December 2016, published online 28 December 2016